Ação de galactomanana sulfatada isolada de Adenanthera pavonina na resposta bioquímica de defesa do feijão-de-corda [Vigna unguiculata (L.) Walp.] desafiado pelo fungo Colletotrichum gloeosporioides - Varela, Anna Lídia Nunes (2012)
Cowpea [Vigna unguiculata (L.) Walp.] is a food of great commercial importance, being the main food source in some regions such as northeastern Brazil. Unfortunately, cowpea is subject to attack by various pathogens and pests, causing considerable losses in productivity. To reduce these losses, there are several chemical methods that are widely used, but the indiscriminate use of fungicides has caused damage to the environment and living beings. In search of alternative environmentally friendly, a promising option would be the induction of defense mechanisms of the plant itself through elicitor molecules. Given the above, this study aimed to elicit defense responses in cowpea through the use of galactomannan isolated from Adenanthera pavonina and induce resistance to Colletotrichum gloeosporioides. Twelve days after germination, cowpea plants (Vigna unguiculata) were treated with A. pavonina galactomannan (at concentrations of 100 mg/L and 200 mg/L) in the absence or presence of the fungus C. gloeosporioides (inoculated 6 hours after treatment with carbohydrate) for 6, 12, 24 and 48 h were carried out on biochemical analysis of protein extracts obtained from primary leaves. For enzymes POX and APX a significant increase occurred after 12 h of treatment with the galactomannan. With respect to antifungal activity of the enzymes and βGLU CHI, the plants treated with the galactomannan in general, showed an increase above 50% compared to control. Macroscopic analysis revealed that the leaves treated with 200 mg/L of galactomannan and infected with C. gloeosporioides showed necrotic lesions visibly reduced compared to control. Furthermore, the galactomannan was unable to inhibit the germination of spores and vegetative growth of the fungus C. gloeosporioides in vitro. The results of the present study indicate that galactomannan isolated from A. pavonina can increase crop tolerance of cowpea (V. unguiculata) against the fungus C. gloeosporioides.